2018
DOI: 10.36253/978-88-6453-672-9.09
|View full text |Cite
|
Sign up to set email alerts
|

The Student Voice in Higher Education and the Implications of Promoting Faculty Development

Abstract: This chapter presents a literature overview of the student voice in higher education, the main results from a three-year research project conducted at five Italian universities with the aim of investigating students’ voices in higher education and how they offer insight into fostering Faculty Development

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…From an educational point of view, the relationship between universities and the world of work can be activated through a range of actions that go from work‐related didactics (Fedeli, ) to the implementation of curricular and extracurricular work experience, underlining how far transversal skills can model the path of a graduate. Indeed, it can be assumed that employability is not a characteristic of people or systems or institutions, but a process, and as such, it must be constructed together, in an organized and responsible manner.…”
Section: From Employability To Educational Actionsmentioning
confidence: 99%
“…From an educational point of view, the relationship between universities and the world of work can be activated through a range of actions that go from work‐related didactics (Fedeli, ) to the implementation of curricular and extracurricular work experience, underlining how far transversal skills can model the path of a graduate. Indeed, it can be assumed that employability is not a characteristic of people or systems or institutions, but a process, and as such, it must be constructed together, in an organized and responsible manner.…”
Section: From Employability To Educational Actionsmentioning
confidence: 99%
“…A survey that included 3,760 students from different universities investigated five areas of interest, which also included the creation of a participatory environment, the use of methods and resources for teaching and learning, and the dimensions of feedback and assessment. Data analysis showed that faculties are still resistant to innovative teaching approaches, how low the level of interaction with students in the form of class discussion and group activities is, and how little feedback and peer-self-evaluation are promoted (Fedeli, 2018). This was the most extensive study done in Italy that included students' voice and opinions on teaching methods in higher education in the last decade.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In Italy, the students' voice perspective has obtained increasing relevance year by year since the 2000s. Many scholars have highlighted its importance, identifying it as a way to create democratic educational environments (Fedeli, 2016(Fedeli, , 2018Grion & Cook-Sather, 2013) and improve educational practices and recognising students as a subsidiary source for the research (Gemma, 2013). They've also found that it promotes discussion practices within the educational contexts because giving a voice to students reinforces two dimensions: the social one, creating strong group integration, but also the introduction of new teaching and learning approaches, such as constant formal and informal feedback to students, peer and self-evaluation, methods and techniques that promote dialogue, students' participation and involvement (Fedeli, 2018).…”
Section: Students' Voice In Education Studies In Italy and In Latviamentioning
confidence: 99%
See 2 more Smart Citations